Circumferential strain by velocity vector imaging and speckle‐tracking echocardiography: validation against sonomicrometry in an aortic phantom. (6th February 2017) - Petrini, Johan; Eriksson, Maria J.; Caidahl, Kenneth; Larsson, Matilda
Summary: Background: Evaluation of arterial deformation and mechanics using strain analysis on ultrasound greyscale images has gained increasing scientific interest. The aim of this study was to validate in vitro measurements of circumferential strain by velocity vector imaging (VVI) and speckle‐tracking echocardiography (STE) against sonomicrometry as a reference method. Method: Two polyvinyl alcohol phantoms sized to mimic the descending aorta were constructed and connected to a pulsatile flow pump to obtain high‐resistance flow profiles. The ultrasound images of the phantom used for strain analyses were acquired with a transesophageal probe. Global and regional circumferential strains were estimated using VVI and STE and were compared with the strain acquired by sonomicrometry. Results: Global circumferential peak strain estimated by VVI and STE correlated well to sonomicrometry ( r = 0·90, P ≤0·001; and r = 0·97, P ≤0·01) with a systematic bias of −0·78% and +0·63%, respectively. The reference strain levels were 1·07–2·54%. Circumferential strain values obtained by VVI were significantly lower than those obtained by STE (bias −1·41%, P ≤0·001). Conclusion: Global circumferential strain measured by VVI and STE correlates well with sonomicrometry. However, strain values obtained by VVI and STE differ significantly, which should be taken into consideration when comparing results from studies using different software for aortic strain measurements.